ABOUT THE METHANE FLUX INTO THE ATMOSPHERE IN THE BIEN DONG (SOUTH CHINA) SEA - B., Shakirov R.; Lan, Nguyen Hong; Mariya, Shakirova (Vietnam Journal of Marine Science and Technology, 2018)
The methane is an active "greenhouse" gas and is a more potent greenhouse gas than CO2, there is over 200 times more CO2 in the atmosphere. Its concentration in the atmosphere is increasing; the mapping of its emission zones in the oil and gas aquifers is one of the important tasks of modern oceanography. In the South China Sea (East Sea, Bien Dong), its basins develops in complex geodynamic conditions, and the water column is characterized by considerable variability of hydrodynamic parameters. The data are obtained for the first time in this research.